2015
DOI: 10.3748/wjg.v21.i24.7522
|View full text |Cite
|
Sign up to set email alerts
|

Use of magnetic resonance elastography for assessing liver functional reserve: A clinical study

Abstract: MRE is accurate and non-invasive; furthermore, it can be used to effectively assess the liver functional reserve of HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…ICG-r15 appears to be accurately related to liver decompensation, confirming the preliminary findings of its association with portal hypertension in compensated patients, and can be used for patient prognostication[36]. Li et al[37] assessed the hepatic functional reserve in patients with HCC through the use of magnetic resonance elastography (MRE). Regions of interest were identified in different slices of the liver parenchyma free of tumour to measure average stiffness.…”
Section: Emerging Non-invasive Assessment Of Extensive Fibrosis or CImentioning
confidence: 82%
“…ICG-r15 appears to be accurately related to liver decompensation, confirming the preliminary findings of its association with portal hypertension in compensated patients, and can be used for patient prognostication[36]. Li et al[37] assessed the hepatic functional reserve in patients with HCC through the use of magnetic resonance elastography (MRE). Regions of interest were identified in different slices of the liver parenchyma free of tumour to measure average stiffness.…”
Section: Emerging Non-invasive Assessment Of Extensive Fibrosis or CImentioning
confidence: 82%
“…Therefore, to evaluate the efficacy of our elasticity map for diagnosing the liver functional reserve, further comparison of our elasticity map with the GSA‐SPECT and ICG clearance tests needs to be performed. Recently, several studies have reported the efficacies of UTE and MRE for diagnosing the liver functional reserve, which are comparable to the GSA‐SPECT and ICG clearance tests 38,71,72 . Therefore, adapting liver elasticity information to radiotherapy planning could be useful in the prevention of RILD; however, additional research is required.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that MRI‐based elastography (MRE) has a predictive ability comparable to that of the histologic staging of liver fibrosis and greater than that of DWI and Gd‐EOB‐DTPA‐enhanced MRI 36,37 . Furthermore, Bin et al 38 demonstrated that MRE examinations can be used to assess the liver functional reserve accurately. However, these functional images provided by MRI, SPECT/CT, and elastography are not routinely acquired in clinical radiotherapy planning.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, it is necessary to perform pathological examination and reserve function evaluation of the donor liver before liver transplantation. Currently, the commonly used methods, such as liver biopsy, serum biochemical index examination and imaging examination (22,23), are not fully applicable due to the diminishing accuracy of liver functional assessment (24,25). Quantitative methods for liver function with high accuracy and practicability, such as the ICG clearance test (26,27), can only be performed on live livers.…”
Section: Discussionmentioning
confidence: 99%